Diffusion-weighted imaging hyperintensities during the chronic stage of intracerebral hemorrhage with surgery: A new clinical situation or post-surgery artifact? - Chen, Xiaoyan; Li, Ying; Guo, Shengli; Han, Xun; Liu, Ruozhuo; Tian, Chenglin; Cui, Rongtai; Dong, Zhao; Yu, Shengyuan (Frontiers in Neurology, 2022)
Background and Objective: Diffusion-weighted imaging (DWI) hyperintensities were occasionally seen at previous hematoma in patients several months after intracerebral hemorrhage with surgery. Whether they are newly-occurred clinical situation or post-surgery changes is unknown. This study aims to investigate the prevalence and possible mechanism for this phenomenon. Methods: We retrospectively reviewed the MRI database for intracerebral hemorrhage with surgery after 3 months of disease onset in our hospital. We also prospectively performed repeated multimodal MRI scans for two patients at the chronic stage after surgery for intracerebral hemorrhage. Results: We found 14 out of 23 patients (60.9%) had DWI hyperintensities at the site of previous hematoma 3 months after intracerebral hemorrhage with surgery. All the DWI lesions were hyperintense on T1 and T2 weighted imaging, most of which appeared long and narrow in shape. The DWI lesions were usually located adjacent to the thin wall of previous hematoma cavity close to the lateral ventricle. They were more associated with the basal ganglia hemorrhage than with the lobar hemorrahge (P=0.02) and were more frequently seen for those with intraventricular hemorrhage than without (P=0.02). Prospectively repeated MRI exams of two patient revealed unchanged DWI hyperintensity during the 18-month and 2-month follow-up, respectively. Conclusion: DWI lesions at previous hematoma were commonly seen in patients after surgery for intracerebral hemorrhage at the chronic stage which would persist for years. We hypothesized a possible mechanism by which extracellular methemoglobin “islands” are formed with delayed or no absorption by macrophages from adjacent thin residual brain tissue. Unnecessary further examinations and treatment would be avoided by realizing this imaging phenomenon.